SYNTHESIS AND INVESTIGATION OF CHARACTERISTICS OF CORROSION INHIBITOR IKMM-1 ST20 STEEL IN 1 M HCl SOLUTION (Multidisciplinary Journal of Science and Technology, 2024)
In this work, we studied the synthesis of the corrosion inhibitor IKMM-1 based on maleic anhydride and monoethanolamine. Corrosion inhibitor was obtained by a weight loss measurement with different concentrations (from 100 mg/l to 400 mg/l) and inhibition efficiency at different temperatures (298, 313 and 323 K) and braking coefficient (γ), surface (θ), determined the values of the degree protection (η).